Mechanism of Recurrence of Atrial Tachycardia - Masateru Takigawa; Nicolas Derval; Claire Martin; Konstantinos Vlachos; Arnaud Denis; Yosuke Nakatani; Τakeshi Kitamura; Ghassen Cheniti; Félix Bourier; Anna Lam; Ruairidh Martin; Antonio Frontera; et al. (2020)
Background: Atrial fibrillation ablation–related atrial tachycardia (AT) is complex and may demonstrate several forms: anatomic macroreentrant AT (AMAT), non-AMAT, and focal AT. We aimed to elucidate the recurrence rate and mechanisms of atrial fibrillation ablation–related AT recurrence. Methods: Among 147 patients with ATs treated with the Rhythmia system, 68 (46.3%) had recurrence at mean 4.2 (2.9–11.6) months, and 44 patients received a redo procedure. AT circuits in the first procedure were compared with those in the redo procedure. Results: Although mappable ATs were not observed in 7 patients, 68 ATs were observed in 37 patients during the first procedure: perimitral flutter (PMF) in 26 patients, roof-dependent macroreentrant AT (RMAT) in 18, peritricuspid flutter in 10, non-AMAT in 14, and focal AT in 3. During the redo AT ablation procedure, 54 ATs were observed in 41/44 patients: PMF in 24, RMAT in 14, peritricuspid flutter in 1, non-AMAT in 14, and focal AT in 1. Recurrence of PMF and RMAT was observed in 15 of 26 (57.7%) and 8 of 18 (44.4%) patients, respectively, while peritricuspid flutter did not recur. Neither the same focal AT nor the same non-AMAT were observed except in 1 case with septal scar–related biatrial AT. Epicardial structure–related ATs were involved in 18 of 24 (75.0%) patients in PMF, 4 of 14 (28.6%) in RMAT, and 4 of 14 (28.6%) in non-AMAT. Of 21 patients with a circuit including epicardial structures, 6 patients treated with ethanol infusion in the vein of Marshall did not show any AT recurrence, although 8 of 15 (53.3%) treated with radiofrequency showed AT recurrence ( P =0.04). Conclusions: Although high-resolution mapping may lead to correct diagnosis and appropriate ablation in the first procedure, the recurrence rate is still high. The main mechanism of atrial fibrillation ablation–related AT is the recurrence of PMF and RMAT or non-AMAT different from the first procedure. Epicardial structures (eg, coronary sinus/vein of Marshall system) are often involved, and ethanol infusion in the vein of Marshall may be an additional treatment.